Breaking primary dormancy in seeds of the perennial pasture legume tedera (Bituminaria bituminosa C.H. Stirt. vars albomarginata and crassiuscula). (17th December 2013) - Castello, M.; Croser, J. S.; Lulsdorf, M. M.; Ramankutty, P.; Pradhan, A.; Nelson, M. N.; Real, D.
Abstract Tedera (Bituminaria bituminosa vars. albomarginata and crassiuscula) is a perennial pasture species with agronomic characters ideally suited to Mediterranean climates. Tedera seed has a period of after‐ripening or primary dormancy typically lasting three months, which delays assessment and breeding of elite hybrid varieties. Temperature, chemical and mechanical methods were investigated in conjunction with in vitro culture to circumvent this dormancy period across a range of parental and hybrid genotypes. Temperature treatment of T5 (Tedera accession 5) and T48 (Tedera accession 48) alone was not sufficient to break dormancy (24.0% and 14.7% germination); however, when combined with soaking in gibberellic acid (GA3) and mechanical scarification resulted in 79.7% and 84.3% germination respectively. In an effort to further improve this result for valuable hybrid genotypes, we combined mechanical scarification with removal of seed coat after imbibition and in vitro culture on B5 medium until radicle emergence. This resulted in breaking dormancy from 96% to 100% of parent seeds and 100% of hybrid seeds. Hardening the germinated F1 or F2 seedlings 4 d after first transfer to in vitro culture resulted in 100% survival of plants to soil. This procedure is now used on a routine basis in the Australian tedera breeding programme.